A Systematic Review of Clinical Outcomes Associated With Intrahospital Transitions. Issue 4 (July 2020) - Bristol, Alycia A.; Schneider, Catherine E.; Lin, Shih-Yin; Brody, Abraham A.
Abstract : ABSTRACT: Previous transitional care research has focused on transitions occurring between community and hospital settings. Little is known regarding intrahospital transitions and how they affect care quality. A systematic review was therefore conducted to synthesize the literature regarding clinical outcomes associated with intrahospital transitions. Literature published between January 2003 and December 2018 and indexed in Medline/PubMed, CINAHL, and PsychINFO were reviewed using PRISMA guidelines. Articles were limited to English language and peer-reviewed. Articles were excluded if they focused on transitions occurring from or to the hospital, discharge/discharge planning, or postdischarge follow-up. Data abstraction included study characteristics, sample characteristics, and reported clinical outcomes. Fourteen studies met inclusion criteria, primarily using cross-sectional, cohort, or retrospective chart review quantitative designs. Data were analyzed and synthesized based on outcomes reported. Major outcomes emerging from the articles included delirium, hospital length of stay, mortality, and adverse events. Delirium, hospital length of stay, and morbidity and mortality rates were associated with delayed transfers and transfers to inappropriate units. In addition, increased fall risk and infection rates were associated with higher rates of transfer. Intrahospital transitions represent critical periods of time where the quality of care being provided may be diminished, negatively affecting patient safety and outcomes.